Effect of load blocks on fatigue crack growth. (September 2022) - Neto, D.M.; Sérgio, E.R.; Borges, M.F.; Borrego, L.P.; Antunes, F.V.
Highlights: The effect of load blocks is predicted numerically using crack tip plastic strain. The numerical model was validated with experimental results for MT specimens made of 6082-T6 aluminium alloy. Crack closure is the main mechanism explaining the transient behaviour. Partial crack closure is important in high-low load blocks and may stop the propagation. Crack tip blunting, due to lack of material hardening explains the effect of LHmin pattern. Abstract: This research studies fatigue crack growth (FCG) in MT and CT specimens made of 6082-T6 aluminium alloy and Ti6Al4V, respectively, submitted to Low-High and High-Low load sequences. A numerical approach based on cumulative plastic strain at the crack tip was followed. A good agreement was found between numerical predictions and experimental results, which validate the assumption that cyclic plastic deformation is the main damage mechanism. Crack closure was able to explain the peak of da/dN in LHmin (Low-High blocks keeping the maximum load), the crack arrest in HLmin load pattern and the decrease of the influence of contact and non-contact conditions with the increase of stress ratio, R. The lack of material hardening is responsible for crack tip blunting which eliminates totally or partially the load history in LHmin patterns. Finally, partial crack closure is observed in high-low load blocks, due to the plastic wake of the first load block, which reduces FCG and may even arrest the crack, particularly in HLmin patterns.